1994
DOI: 10.1007/bf00039304
|View full text |Cite
|
Sign up to set email alerts
|

Freeze preservation of gladiolus pollen

Abstract: Viability and fertility profiles of cryopreserved gladiolus pollen from 7 cultivars have shown that it is possible to use cryogenic methods for conservation and management of the haploid gene pool in this species. There was no decline in pollen viability (in vitro) levels after 1 and 10 years of cryogenic storage. Field pollinations with cryogenic stored pollen induced capsule and seed set in varying capacities. Long-term cryogenic storage of gladiolus pollen could enhance breeding efficiency through better ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…In tests carried out in vitro after 3 months of storage, germination did not exceed 11%, with no significant effect of temperature (data not shown). However, pollen that does not germinate well on media suitable for freshly collected pollen is not necessarily nonviable Rajasekharan et al, 1994;Shivanna and Rangaswamy, 1992) and may produce satisfactory fruit set. Moreover, if the pollen load on the stigma is adequate, a sufficient number of pollen grains will be able to ensure fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…In tests carried out in vitro after 3 months of storage, germination did not exceed 11%, with no significant effect of temperature (data not shown). However, pollen that does not germinate well on media suitable for freshly collected pollen is not necessarily nonviable Rajasekharan et al, 1994;Shivanna and Rangaswamy, 1992) and may produce satisfactory fruit set. Moreover, if the pollen load on the stigma is adequate, a sufficient number of pollen grains will be able to ensure fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction effect of cryopreserved pollen-cum-Psittacinus hybrid x Kum Kum produced minimum number of underdeveloped seeds (8.00 per capsule) which was on par with cryoprerved pollen-cum-Hybrid selection 88-10-22 x Shobha (8.88 per capsule), and fresh pollen-cumPsittacinus hybrid x Kum Kum (9.56 per capsule). Rajasekharan et al (1994) observed comparatively high number of seeds per capsule under fresh pollen used in cross combinations viz. Sapna x Meera, Shobha x Meera and Meera x Aspara.…”
Section: Interaction Effect Of Pollen (Fresh or Cryopreserved) And Crmentioning
confidence: 92%
“…In tests carried out in vitro after 3 months of storage germination did not exceed 11%, with no significant effect of temperature (data not shown). However, pollen that does not germinate well on media suitable for freshly collected pollen is not necessarily nonviable (Polito and Luza, 1988;Rajasekharan et al, 1994;Shivanna and Rangaswamy, 1992) and may produce satisfactory fruit set. Moreover, if the pollen load on the stigma is adequate, a sufficient number of pollen grains will be able to ensure fertilization.…”
Section: Resultsmentioning
confidence: 99%